Optimasi Sizing Kolom Stripper Menggunakan Variasi Solvent dan Flow Rate Natural Gas Pada Aspen Hysys - Furqon, Zami; Rizky A.P., Dimas Hardian; Setiyono, Agus (Jurnal Permadi : Perancangan, Manufaktur, Material dan Energi, 2025)
This research was conducted to optimize changes in Stripper column sizing to variations in solvent and natural gas flow rate in the Acid Gas Removal Unit (AGRU) at PT. X. The aim of this research is to determine the optimal size of the Stripper column which can increase the efficiency of the acid gas removal process in natural gas streams. The methodology used includes experimental analysis and simulation using process modeling software. Several different types of solvents and variations in natural gas flow rates were tested to see their effect on the performance of the Stripper column. Based on the results of the hydraulic profile of the tray in the Stripper column with the MDEA solvent variation, it can be concluded that the tray operation is in a safe and efficient condition. The data shows that the % Jet Flood value is within the maximum range of up to 47.96% of all flow rate variations, which is far below the maximum specification limit of 100%. In the optimization results of the Sulfolane+MDEA variation, results were obtained where the operating point of the tray was at a balance point where no weeping occurred, because the optimized results were marked by the hydraulic graph plot point being above the weeping point line, so that no weeping occurred on the tray and no flooding occurred. because the maximum jet flooding % value of the three flow rate variations on the tray is 30.05%. This result is far from the maximum limit, which is 100%, so the column works in non-flooding conditions. The research results show that the optimal Stripper column size depends on the type of solvent used and the natural gas flow rate.